The Impact of Augmented Reality on E-Commerce Platforms - Chadha, Janisha (International Journal of All Research Education and Scientific Methods (IJARESM), 2022)
With the development of augmented reality (AR) technology, marketers now have interesting new chances to interact with consumers and alter the way they perceive their brands. Businesses are justifiably eager to invest and employ AR in their own business model due to the dearth of studies reflecting its pragmatic advantages in daily scenarios. This paper provides two conceptual applications of the technology in retail contexts. The first is the very application of augmented reality to fortify product evaluation prior to purchase, and the other pertains to researching its effects on sales in online shopping. Using data from global retailer stores such as IKEA and Lenskart, it is discovered that using AR on the retailer's mobile app is linked to increased sales for less well-known brands, more niche appealing goods, and more costly products. Additionally, clients who are new to the online channel or a certain product category would be able to better understand its functionality via AR, which suggests that the growth in sales is the result of online channel adoption and category development. These results demonstrate the technology's potential to improve sales by reducing doubt and establishing purchasing confidence, showing that AR is most successful when product-related ambiguity is high. The paper further explores the limitations of the usage of AR namely complexities in usage, especially for older consumers who don't have profound technological knowledge. Besides discussing the significant increase in customer engagement due to the presence of augmented reality which would aid in generating more digital traffic and search engine optimization. The benefits of reduced return rates, insinuating lower overhead costs as a result of AR have also been extensively discussed.
ISME
Keywords: Augmented reality; electronic commerce (e-commerce); technology; business-to-consumer (B2C)